Refigured Painting : The German Image 1960-88 - Krens, Thomas; Govan, Michael; Thompson, Joseph; Solomon R. Guggenheim Museum, New York; The Toledo Museum of Art, Toledo; Williams Collega Museum of Art, Williamstown; Kunstmuseum Düsseldorf; Kunsthalle Frankfurt (München : Prestel Verlag, 1989)
Albert, Hermann ; Antes, Horst ; Bach, Elvira ; Barfuss, Ina ; Baselitz, Georg ; Bömmels, Peter ; Büttner, Werner ; Chevalier, Peter ; Dahn, Walter ; Dokoupil, Jiri Georg ; Fetting, Rainer ; Hacker, Dieter ; Hahn, Friedemann ; Hartmann, Thomas ; Herold, Georg ; Hödicke, K.H. ; Immendorff, Jörg ; Kasseböhmer, Axel ; Kiefer, Anselm ; etc.
Refigured Painting : The German Image 1960-88, The Toledo Museum of Art, Toledo, Ohio (October 30, 1988 - January 8, 1989) ; Solomon R. Guggenheim Museum, New York, (February 11 - April 23, 1989) ; Williams Collega Museum of Art, Williamstown, Massachusetts (February 11 - March 26, 1989) ; Kunstmuseum Düsseldorf (May - July 1989) : Schirn Kunsthalle, Frankfurt (September - November 1989)
English
kunstcatalogus
Keywords: Duitsland